1999
DOI: 10.1021/ja9901821
|View full text |Cite
|
Sign up to set email alerts
|

The Palladium-Catalyzed Enyne Cycloisomerization Reaction in a General Approach to the Asymmetric Syntheses of the Picrotoxane Sesquiterpenes. Part I. First-Generation Total Synthesis of Corianin and Formal Syntheses of Picrotoxinin and Picrotin

Abstract: The palladium-catalyzed enyne cycloisomerization is used as a key ring-forming process for the obtention of the cis-fused hydrindane carbon skeleton characteristic of the picrotoxanes sesquiterpenes. The enyne cycloisomerization product is suitably functionalized so that each carbon of the hydrindane core can be modified to permit access to many members of the picrotoxane family, not only to picrotoxinin itself. Part I of this report describes our first-generation approach to the picrotoxane sesquiterpenes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…Trost and coworkers have demonstrated its use in their synthesis of corianin. 34 The Cao group likewise has shown the use of CH 2 O in aldol reactions en route to a total synthesis of malyngamide U. 35 After significant experimentation in our system, we found that bubbling gaseous CH 2 O (generated by the pyrolysis of paraformaldehyde) through a solution of the lithium enolate of 40 at −45 °C furnished the desired primary alcohol 41 in 70% yield.…”
Section: Resultsmentioning
confidence: 86%
“…Trost and coworkers have demonstrated its use in their synthesis of corianin. 34 The Cao group likewise has shown the use of CH 2 O in aldol reactions en route to a total synthesis of malyngamide U. 35 After significant experimentation in our system, we found that bubbling gaseous CH 2 O (generated by the pyrolysis of paraformaldehyde) through a solution of the lithium enolate of 40 at −45 °C furnished the desired primary alcohol 41 in 70% yield.…”
Section: Resultsmentioning
confidence: 86%
“…Among them, picrotoxinin (106) (Scheme 9) is known to be a potent and specific inhibitor of the antagonist of the neurotransmitter suppressor -aminobutyric acid (GABA). Trost et al synthesized Yoshikoshi intermediate 76 [14] for picrotoxane synthesis employing their original palladium catalyzed ene-yne cycloisomerization as a key reaction (Scheme 6) [15].…”
Section: Diels-alder Reaction Of S-(+)-carvonementioning
confidence: 99%
“…Corey's intermediate 80 [16] for picrotoxane synthesis was also synthesized from the same PMBO derivative of 73 (Scheme 7) [14]. Allyl inversion provided chloride 77, which was transformed into triol 78 after substitution with cesium acetate, followed by deprotection.…”
Section: Diels-alder Reaction Of S-(+)-carvonementioning
confidence: 99%
“…However, smooth cyclization took place to give the Alder-ene product in a quantitative yield at 50 • C when N ,N -bis(benzylidene)ethylenediamine (BBEDA) was used as a ligand, and the triol 142 was obtained in 75 % yield after deprotection, and the asymmetric synthesis of picrotoxinin has been carried out. The effect of the BBEDA ligand is remarkable [44]. The cycloisomerization of 1,6-enynes proceeds smoothly in the presence of AcOH or HCO 2 H and the reaction is explained by the following mechanism (hydridopalladium acetate mechanism) [45].…”
Section: Palladacycle Mechanismmentioning
confidence: 99%